(untitled) - LARASATI, NIKEN (RETAIN : Journal of Research in English Language Teaching, 2015)
Abstract The goal of this study is to present the implementation of ‘Three-Step Interview’ modified group of four in teaching speaking recount text. This study was conducted in one class, VIII-H, that consists 37 students. There was only experimental class without control class. This study used pre-experimental research design by using one group pretest-posttest design. The data were obtained from two students’ speaking tests before and after the treatment and the questionnaire. The findings of the study show that: (1). the students’ speaking skill shows improvement after they are taught by using ‘Three-Step Interview’, (2). from the questionnaire, it is revealed students’ opinion that they mostly agree the implementation of ‘Three-Step Interview’ for teaching speaking brings the positive effect. It could be concluded that ‘Three-Step Interview’ helps the students in improving their speaking skill and the students get the advantages of ‘Three-Step Interview’. Keywords: ‘Three-Step Interview’, Speaking Skill, Students’ view. Abstrak Studi ini bertujuan untuk memperkenalkan implementasi ‘Three-Step Interview’ dengan modifikasi empat anggota kelompok dalam pengajaran berbicara Bahasa Inggris teks recount. Studi ini diadakan dalam satu kelas yaitu kelas VIII-H dengan jumlah 37 siswa. Studi ini hanya menyediakan kelas eksperimental tanpa adanya kelas kontrol. Desain penelitian yang digunakan adalah pre-eksperimental yang disebut dengan desain one-group pretest-posttest. Data studi ini diperoleh dari dua test percakapan siswa sebelum adan sesudah tindakan pelaksanaan ‘Three-Step Interview’ dan angket daftar pertanyaan. Hasil dari studi ini menunjukkan bahwa: (1). kemampuan percakapan siswa menunjukkan perbaikan atau kemajuan setelah siswa-siswa diberi pengajaran dengan menggunakan ‘Three-Step Interview’, (2). Dari angket daftar pertanyaan menunjukkan pendapat siswa bahwa sebagian besar siswa-siswi setuju pelaksanaan ‘Three-Step Interview’ dalam pengajaran percakapan membawa efek yang positif. Dari hasil yang telah disebutkan, dapat disimpulkan bahwa ‘Three-Step Interview’ dapat membantu siswa dalam kemajuan berbahasa Inggris dan siswa mendapatkan manfaat dari ‘Three-Step Interview’. Kata Kunci: ‘Three-Step Interview’, kemampuan berbicara, pendapat siswa.